Reconsidering Teaching Construction in Architectural Education - Sardar S. Shareef; Hozan Latif Rauf; Ejeng Bassey Ukabi (Engiscience Publisher, 2024)
This paper critically examines the weakening connection between design and construction in architectural education, highlighting the underrepresentation of construction courses in comparison to their design counterparts. By analyzing contemporary pedagogical methods, it aims to uncover a more effective teaching approach that simultaneously nurtures students' enthusiasm for construction and design, emphasizing the synergy between technical proficiency and creative vision. Proposing a hands-on, problem-solving methodology integrated within design studios, this study suggests a paradigm shift towards an ontological observational approach. It argues for a transformative change in perception among educators and students alike, advocating for a unified educational framework that fosters technical and theoretical coherence, ultimately contributing to sustainable architectural practices.